1988
DOI: 10.1002/jmv.1890250110
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and significance of hepatitis B core antibody in a healthy blood donor population

Abstract: To determine the current incidence of hepatitis B core antibody (anti-HBc) in a healthy blood donor population, 1,893 donors were screened for anti-HBc. Forty-one (2.16%) were found to be initially positive and 35 (1.85%) repeatably positive. Sera from the repeatably positive donors were further screened for hepatitis B surface antibody (anti-HBs), and hepatitis B virus DNA (HBV DNA) by dot hybridisation. The repeatably positive donors were subsequently recalled for further investigation, and their peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…For homosexuals carrier prevalence is an order of magnitude greater than for heterosexuals, and between about 5 % (at [15][16][17][18][19][20] years) and 55 % (at 55-60 years) show history of infection. Table 3 provides an indication from published sources [16][17][18][19][20][21][22][23][24][25][26][27] ever infected, comparison with Figure 4 suggests that the model results are, in general, consistent with levels observed in the UK population. Figure 5 shows the predicted proportion of individuals who are chronic carriers of HBV stratified by sexual activity class (1 is lowest, 6 is highest), for heterosexuals (light bars) and homosexuals (dark bars).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…For homosexuals carrier prevalence is an order of magnitude greater than for heterosexuals, and between about 5 % (at [15][16][17][18][19][20] years) and 55 % (at 55-60 years) show history of infection. Table 3 provides an indication from published sources [16][17][18][19][20][21][22][23][24][25][26][27] ever infected, comparison with Figure 4 suggests that the model results are, in general, consistent with levels observed in the UK population. Figure 5 shows the predicted proportion of individuals who are chronic carriers of HBV stratified by sexual activity class (1 is lowest, 6 is highest), for heterosexuals (light bars) and homosexuals (dark bars).…”
Section: Resultsmentioning
confidence: 70%
“…Published data on the prevalence of HBV markers has been reviewed and used to provide a check on the model predictions of endemic prevalence of infection. A summary of these data is shown in the results section (Table 3) [16][17][18][19][20][21][22][23][24][25][26][27], illustrating the wide range in marker prevalence for different risk groups in the population. The available serological data is, however, very coarsely stratified by age, if at all, and is often not representative of the wider heterosexual or homosexual populations.…”
Section: Introductionmentioning
confidence: 99%
“…8 Other studies have suggested a falsepositive rate for isolated anti-HBcAg positivity of from 20% to 50%. 2,9 The simultaneous presence of anti-HBsAg or HbsAb likely indicates a true positive anti-HBcAg antibody, 10 as does a higher titer (not usually reported) of anti-HBcAg 6 and positivity by radioimmunoassay (RIA; CoreAB, Abbott Laboratories, North Chicago, IL), as compared with positivity by the more frequently used EIA (Corzyme Abbott Laboratories, North Chicago, IL). 11 Of note, anti-HBsAg was present in all anti-HBcAg-positive donors implicated in hepatitis B transmission in both the report from Douglas and Wachs.…”
Section: Screening Methodsmentioning
confidence: 99%
“…The phenomenon of isolated anti-HBc has been examined by others before [Kitchen et al, 1988;Parkinson et al, 1990;Lai et al, 19901, but the number of cases was usually small. In the present study a large series of prospectively obtained serum samples was tested from a population considered to be at high risk of infection as compared to healthy blood donors.…”
Section: Introductionmentioning
confidence: 98%
“…The phenomenon of isolated anti-HBc has been examined by others before [Kitchen et al, 1988;Parkinson et al, 1990;Lai et al, 19901, but the number of Nonspecific assay, causing false-positive result of anti-HBc Core window, phase of acute infection before appearance of anti-HBs Remnant antibody, anti-HBc remaining as sole marker after loss of anti-HBs and anti-HBe Suppression of HBsAg with HDV infection Antigenic variant of HBsAg phase possibly infectious infectious cases was usually small. In the present study a large series of prospectively obtained serum samples was tested from a population considered to be at high risk of infection as compared to healthy blood donors.…”
Section: Introductionmentioning
confidence: 99%